A study on the application technology of the sterile insect technique, with focus on false codling moth, Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae), a pest of citrus in South Africa - Nepgen, Eugene Stephan (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2014)
False codling moth (FCM), Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) is considered the most important indigenous pest of citrus in southern Africa. Major concerns such as progressive insecticidal resistance, the negative impact of insecticides on the environment, as well as the influence of consumers opposed to chemical residues on fruit, created opportunities for biological control methods such as Sterile Insect Technology (SIT). This technology is now established in the Western and Eastern Cape provinces of South Africa as an effective, sustainable alternative to conventional FCM control methods. Due to the prevalence of the pest in all citrus producing areas of South Africa, potential for SIT to expand is enormous. Success of an SIT programme is highly dependent on efficient application of the technology to achieve its objectives in a timeous manner. The aim of this study was to advance the application of SIT for control of FCM on citrus in South Africa, by investigating the effect of certain critical stages in the process. The effect of long-distance transportation on fitness of irradiated FCM was determined, showing reduced performance with cold-immobilized transport. A significant decrease in flight ability and longevity of irradiated FCM was found, although critically, realized fecundity was not affected. The effect of two different insecticides in the pyrethroid and organophosphate chemical groups were investigated for their residual effect on mortality of released irradiated FCM, to determine if these pest control programmes could be integrated. Both chlorpyrifos and tau-fluvalinate were effective in killing irradiated FCM for a number of days after application, after which degradation of the active ingredient rendered it harmless. This effect was found to be similar for irradiated and non-irradiated males, consequently ratios of sterile : wild male FCM should be retained regardless of whether sprays are applied or not. The modes for release of sterile FCM in an SIT programme were investigated. Efficacy of ground and aerial release platforms were tested by evaluating the recovery of released irradiated male FCM in these orchards. More irradiated FCM were recovered in orchards released from the ground compared to air. However, an economic analysis of both methods shows application of irradiated insects over a large geographical area is more cost-effective by air. Depending on the terrain and size of the target area, a combination of both methods is ideal for application of SIT for control of FCM in citrus. Development of application technology for advance of the programme is discussed and recommendations for future research and development are offered.
Keywords: Cryptophlebia leucotreta; Citrus -- Diseases and pests -- Control -- South Africa; Insect pests -- Control -- South Africa; Insect sterilization